Psychiatric comorbidity in substance abusing population in Garhwal hills of Uttarakhand - Singh, Prem; Rathi, Harsh; Mishra, Anjali (International Journal of Research in Medical Sciences, 2020)
Background: Psychiatric morbidity occurs more frequently in patients with substance abuse than in the general population. Routine evaluation and treatment of psychiatric morbidity can be helpful in improving care of substance abusing population but such data are relatively meager from developing countries. Methods: This study was conducted in the Out-patient facility of the Department of Psychiatry, Veer Chandra Singh Garhwali Government Institute of Medical Science & Research, Srinagar (Uttarakhand), starting from 23 September 2015. One hundred consecutive treatment seeking subjects fulfilling international classification of diseases and related health problems, 10th Revision (ICD-10), criteria for mental and behavioral disorders due to psychoactive substance use were included in the study. All the participants were required to sign an informed consent approved by the institutional ethical committee before being enrolled in the study. All the subjects included in the study were administered a semi-structured Proforma to elicit the clinical and socio-demographic variables. Results: One hundred patients consisting of 95 men (95%) and 05 women (05%) were included. The average age of the sample was 39.68 years (SD=11.97). As for the socio-demographic variables other than age, 87% of the patients were married, 62% patients were living in nuclear families and 66% belonged to the rural areas. 79% patients were educated up to high school and above and only 06% were illiterate. 36 % of the subjects screened positive for psychiatric morbidity. Psychiatric morbidity was significant higher in unmarried people with less education (primary or less) and those living in nuclear families. Conclusions: Psychiatric comorbidity was found in 36% of the study subjects.